Evaluating the relationship between caregiver depression, social support, and children’s internalizing and externalizing symptoms in families affected by 22q11.2 deletion syndrome - Holly Carbyn; Abiaz Hossain; Raquel L. Dias; Lisa D. Palmer; Sophie Ayoub; Patricia Lingley-Pottie; Patrick J. McGrath; Andrea L. Rideout; Andrea Shugar; Cheryl Cytrynbaum; Donna M. McDonald-McGinn; Ann Swillen; et al. (Orphanet Journal of Rare Diseases)
Abstract Background 22q11.2 Deletion Syndrome (22q11DS) is the most common microdeletion syndrome. It exhibits broad phenotypic variability, often including conditions like autism spectrum disorder and intellectual disability. Caregivers of children with 22q11DS are known to be at increased risk of poor mental health and less social support, which might affect their children’s health. The current study examined the relationship between parental mental health, perceived social support, and child mental health (internalizing/externalizing symptoms) in children with 22q11DS. Method Ninety caregivers of children with 22q11DS completed an online survey measuring parental depressive symptoms, perceived social support, and child mental health problems (internalizing and externalizing symptoms). Structural equation models were run to examine the postulated relationships between variables. Results The caregiver’s depressive symptoms were associated with higher internalizing and externalizing symptoms in their children with 22q11DS (mean age 11.8, SD 7.6 years). Caregivers experiencing symptoms of depression were less likely to report strong social support, and lower perceived social support was associated with greater child internalizing and externalizing symptoms. The relationship between caregiver’s depressive symptoms and internalizing symptoms in their children was mediated by perceived social support, but no such mediating effects were observed for externalizing symptoms. Conclusions These findings provide valuable insights into the mental health burdens facing families living with 22q11DS. Interventions focusing on 22q11DS should integrate techniques to foster social and other supports to improve the mental health of caregivers and children.